In Vitro Skin Permeation Efficiency Study on Natural Flavornoid Extracts Incorporated into Nano-Emulsions - Ling, Ing-May; Li, Wen-Hsin; Wang, Lai-Hao (Asian Journal of Chemistry, 2010)
Stable emulsions made with proper types and amounts of surfactants, fatty acids and water have been obtained. By varying the surfactant types (AOT, Brij 30 and HCO 040), concentrations of surfactants (2 to 10 %) and types of fatty acids (lauric acid C12, myristic acid C14, palmitic acid C16 and stearic acid C18), the best emulsions have been obtained by using AOT at 6 % and fatty acid C12 kept at 0.85 % (by weight) oil-to-water (O/W) ratio in a PIT (Phase Inversion Temperature) emulsification method. Emulsions obtained by using Brij 30 AOT at 6 % and fatty acid C12 kept at 0.85 % O/W ratio are also stable and satisfactory. The HLB (hydrophilic-lipophilic balance) temperature for the AOT at 6 % and C12 kept at 0.85 % O/W ratio is 38 ºC. This method produces emulsion droplet sizes ranging from 170 to 290 nm with the average at 230 nm, which has been verified by using a high resolution optical microscope. The droplets are near circular and the emulsification process is homogeneous. Therefore, this emulsion can be classified as a nanoemulsion. Natural, ultra-violet absorbing flavornoid extracts from herbal plants have been incorporated into the emulsion samples made by using AOT at 6 % and fatty acid C12 kept at 0.85 % O/W ratio. In vitro skin permeation experimental results by incorporating Cinnamomum japonicum Sieb and Sophora japonica L extracts indicate that the most effective flavornoid extract concentrations for both ingredients are around 2 %, with the first ingredient performing better than the latter.